Pengaruh Pemahaman Sistem Informasi Akuntansi, Motivasi, Dan Disiplin Kerja Terhadap Kinerja Pegawai Bagian Keuangan Satuan Kerja Perangkat Daerah (SKPD) Kabupaten Tulungagung - Faradila Pratiwiningtyas; Adi Prasetyo (Universitas Muhammadiyah Malang, 2018)
This research aims to demonstrate the effect of understanding accounting information systems, motivation, and work discipline on employee performance. The population in this research is the department at regional units of Tulungagung regency. The sample in this research is the finance department employee of Tulungagung regency. The variable in the research independent variables is understanding accounting information systems, motivation, and work discipline, the dependent variable in the employee performance. Data were analyzed using double linear regression. Data were analyzed using SPSS. The results show that the understanding accounting information system has no significant effect on employee performance. This is evidenced by probability value (p-value) 0,263 on the significant 0,05. The results of research next are motivation and work discipline significant effect on employee performance. This is evidenced by probability value (p-value) 0,005 and 0,001 on the significant 0,05.